The Impact of implementing the Public Entities Corporate Governance Act (PECG Act) Chapter 10:31 by State Owned Enterprises (SOEs) in Zimbabwe. - Admire Mthombeni; Sifile Obert; Mbizi Rangarirai; Malesela Masenya (Center for Risk Management & Sustainability and RSF Press, 2023)
Corporate scandals have become widespread, leading to the downfall of major companies globally. Poor corporate governance practices have sparked significant controversies in several State-Owned Enterprises (SOEs) in Zimbabwe. The study sought to determine the impact of the Public Entities Corporate Governance Act Chapter 10:31(PECG Act). The Act is the main piece of legislation governing corporate governance practices for State Owned Enterprises in Zimbabwe. In this view, the study adopted a mixed-methods approach in which pragmatism philosophy was applied. A convergent parallel design employed using a structured questionnaire and an interview guide. The target population consisted of top and middle management, board members, board chairpersons, and CEOs of SOEs found in Zimbabwe. A sample size of 351 individuals was determined for quantitative data using stratified random sampling, and 16 interviews by purposive sampling. SPSS version 23 was used to analyze quantitative data, whilst NVivo version 12 was used to analyze qualitative data. The main impact of the PECG Act was that it fosters accountability, transparency, and responsibility and encourages strategic planning for SOEs. The study confirmed that reforms on restrictions on the remuneration of board members (RRORB) have a positive effect on corporate governance practices in SOEs, and reforms on dismissal and resignation (RDRBM) of board members lead to best corporate governance in SOEs. This study recommended that responsible authorities should make strict enforcement to comply with the dictates of the PECG Act.